Marble memorials, West wall - Ghosh, Ayan (2023)
St. Thomas Church was dedicated to the spiritual needs of the Anglican community living within Bombay Fort. The foundation stone was laid by Governor Gerald Aungier, who pressed for the establishment of the church. Among the historic treasures kept at the church is a silver chalice presented by Gerald Aungier to the Anglican Christian community in 1675.